2007
DOI: 10.1194/jlr.m600525-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

CLA differently regulates adipogenesis in stromal vascular cells from porcine subcutaneous adipose and skeletal muscle

Abstract: Conjugated linoleic acid (CLA), a mixture of isomers of linoleic acid, has previously been shown to be able to decrease porcine subcutaneous (SC) adipose tissue levels while increasing the count of intramuscular (IM) adipose tissue in vivo. However, the underlying mechanisms through which it acts are poorly understood. The objective of this study was to investigate the different effects of CLA on adipogenesis in cultured SC adipose tissue and IM stromal vascular cells obtained from neonatal pigs. As shown here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 57 publications
3
46
1
Order By: Relevance
“…Meadus et al (2002) have also reported increased PPAR'y and PABP4 mRNA expression in the muscle of barrows fed CLA. Stromal vascular cells isolated from pork loin intramuscular adipose tissue and differentiated in vitro have responded to supplemental GLA in culture with increased mRNA expression of PPAR'y and PABP4 as well (Zhou et al, 2007). Our results are consistent with these other reports even though they did not reach a statistically significant P-value, likely a result of our small sample size.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Meadus et al (2002) have also reported increased PPAR'y and PABP4 mRNA expression in the muscle of barrows fed CLA. Stromal vascular cells isolated from pork loin intramuscular adipose tissue and differentiated in vitro have responded to supplemental GLA in culture with increased mRNA expression of PPAR'y and PABP4 as well (Zhou et al, 2007). Our results are consistent with these other reports even though they did not reach a statistically significant P-value, likely a result of our small sample size.…”
Section: Resultssupporting
confidence: 91%
“…Increased mRNA expression of adipocyte-specific genes PPAR^ and adipocyte fatty acid binding protein 4 {FABP4) were reported in the muscle of GLA-fed pigs (Meadus et al, 2002), suggesting increased adipocytes. This is also supported by cell culture where cells isola,ted from porcine intramuscular adipose tissue increased adipocyte gene exjaression and lipid accumulation, whereas cells isolated irom subcutaneous adipose tissue decreased lipid accumulation and gene expression in response to irans-10,cJs-12 GLA (Zhou et al, 2007). ' Our objective was to determine whether the increase in marbling in GLA-fed pigs was attributable to changes in intramuscular adipocytes.…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, CLA did not affect proliferation of porcine primary SV cells (McNeel and Mersmann, 2003;Zhou et al, 2007), and Ding et al (2000Ding et al ( , 2002 reported increased differentiation in CLAtreated porcine primary cultures. This effect may be depot-specific as porcine SV cells isolated from subcutaneous adipose tissue responded to CLA treatment with reduced adipocyte-specific gene expression and lipid accumulation, but SV cells isolated from intramuscular adipose tissue had greater adipocyte gene expression following CLA treatment (Zhou et al, 2007). A likely mechanism by which CLA influences preadipocyte differentiation is by interacting with PPARγ.…”
Section: Nutritional Regulation Of Adipocytesmentioning
confidence: 95%
“…PPARγ is the main gene responsible for regulating the adipocyte specific genes and is required for adipose differentiation in mice (Rosen et al, 1999). Although the complete mechanism behind this gene expression regulator is not fully understood, various ligands (such as conjugated linoleic acid) have shown to decrease the activity of this gene, decrease subcutaneous preadipocyte formation, and increase intramuscular preadipocyte formation, or marbling (Moya-Camarena, Vanden-Heuvl, Blachard, Leesnitzer, & Belury, 1999;Zhou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%